2018
DOI: 10.1002/dvg.23093
|View full text |Cite
|
Sign up to set email alerts
|

Compound mutations in Bmpr1a and Tak1 synergize facial deformities via increased cell death

Abstract: BMP signaling plays a critical role in craniofacial development. Augmentation of BMPR1A signaling through neural crest-specific expression of constitutively active Bmpr1a (caBmpr1a) results in craniofacial deformities in mice. To investigate whether deletion of Tak1 may rescue the craniofacial deformities caused by enhanced Smad-dependent signaling through caBMPR1A, we generated embryos to activate transcription of caBmpr1a transgene and ablate Tak1 in neural crest derivatives at the same time. We found that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…We reported that Tak1 ‐deficient mutants display a round skull, hypoplastic maxilla and mandible, and cleft palate . Interestingly, deletion of Tak1 aggravates the craniofacial deformities of caBmpr1a;P0‐Cre mutants that have craniosynostosis . Those cKO mice die during the perinatal period precluding functional assessment of TAK1 during postnatal tooth development including secondary dentin formation; therefore, addressing the function of TAK1 with inducible gene targeting systems will provide additional insights into how BMP‐non‐Smad signaling regulates postnatal dentinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that Tak1 ‐deficient mutants display a round skull, hypoplastic maxilla and mandible, and cleft palate . Interestingly, deletion of Tak1 aggravates the craniofacial deformities of caBmpr1a;P0‐Cre mutants that have craniosynostosis . Those cKO mice die during the perinatal period precluding functional assessment of TAK1 during postnatal tooth development including secondary dentin formation; therefore, addressing the function of TAK1 with inducible gene targeting systems will provide additional insights into how BMP‐non‐Smad signaling regulates postnatal dentinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(32) Interestingly, deletion of Tak1 aggravates the craniofacial deformities of caBmpr1a; P0-Cre mutants that have craniosynostosis. (33) Those cKO mice die during the perinatal period precluding functional assessment of TAK1 during postnatal tooth development including secondary dentin formation; therefore, addressing the function of TAK1 with inducible gene targeting systems will provide The region was determined from the cemento-enamel junction that extended 100 μm toward coronal direction (crown thickness) or apical direction (root thickness). Reduced crown dentin thickness in the Bmpr1a cKO molars was restored in the compound mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Deficient activation of the p38 pathway observed in BMPR1A R406L ‐expressing chondrocytes results in loss of Sox9 expression; however, it may contribute to the apoptosis phenotype observed in our cell culture. Mouse studies have shown that compound mutations in constitutively active Bmpr1a and loss of function of TAK1 (upstream of p38 activation) exacerbate deformities via increased cell death (Liu et al, ). Moreover, loss of noncanonical signaling via TAK1 in developing nasal cartilage results in enhanced p‐Smad1/5/8 levels, a phenotype similar to our cell transfection study (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Smads then regulate transcription within the nucleus (Shi & Massagué, ). BMPs are also involved in the activation of TAK1 and downstream effectors including p38 (Greenblatt, Shim, & Glimcher, ; Greenblatt, Shim, Zou, et al, ; Liu et al, ). Bone Morphogenetic Protein Receptor Type1A (BMPR1A) (OMIM: 601299) is one of the crucial membrane receptors of this pathway in skeletal tissues (Rigueur et al, ; Yoon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, our recent studies demonstrated that both P0-Cre and Wnt1-Cre differentially target neural crest cells emerging at the anterior, middle and posterior portions of the head during embryogenesis ( Chen et al, 2017 ). Previously, we reported a neural crest-specific disruption of TGF-beta activating kinase 1 ( Tak1 ) using Wnt1 - Cre and P0 - Cre , respectively ( Yumoto et al, 2013 ; Liu et al, 2018 ). While Tak1 P0 mutants do not show overt craniofacial phenotypes at birth ( Liu et al, 2018 ), Tak1 Wnt1 mutants develop cleft palate secondarily to the micrognathia ( Yumoto et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%